ХАРАКТЕРИСТИКА ПОНЯТИЙ «АВТОРСКОЕ ПРАВО И ОТДЕЛЬНЫЕ АВТОРСКИЕ ПРАВОМОЧИЯ» - Azhibayev, M.G.; Tarihov, D.N. (Journal of actual problems of jurisprudence, 2019)
Questions rise in this article about feature notion «copyright and separate author's authorities».